Strategy to Increase Market Share Current Account Saving Account (CASA) Through Optimizing the Development of Electronic Banking in Indonesia - Yunus, Somi Mohamad (Almana : Jurnal Manajemen dan Bisnis, 2024)
The basis of this research is motivated by the phenomenon that occurs where banking services in Indonesia have still known for a very long time and require a struggle to make a transaction. A network that is often problematic, strict regulations and the length of the account creation process are some examples of problems related to banking services in Indonesia. This study aims to find out how the development of electronic banking at Bank BJB, the Market Share Current Account Savings Account at Bank BJB, what obstacles are faced in the development of electronic banking at Bank BJB, and what strategies are carried out to increase CASA market share through the optimization of electronic banking development. The research method used is qualitative by interviewing resource persons from within the company, policymakers, and practitioners in the banking sector. The results obtained show that Bank BJB has carried out digital service transformation specifically in 2021. The company has made several developments in terms of core banking, switching, and networking. CASA's market share has not reached the expected target. Several strategies to increase Bank BJB's CASA market share through electronic banking optimization include the development of a user-friendly Mobile application. Focus on developing an intuitive and easy-to-use mobile app.